Reducing the dead zone in the hammer landing sector - Umegaki, K.; Murofushi, K.; Murofushi, S.; Sakurai, S.; Seki, Y.; Kimura, Y. (New Studies in Athletics, 2009)
Over the last 60 years, the IAAF has reduced the angle of the hammer throw landing sector and altered the requirements for the design of the safety cage. The main aim has been to increase the safety of athletes and officials by reducing the danger zone in which mis-thrown hammers could possibly land. However, recent changes have lead to a number of problems, the most important being an effective reduction of the landing area, which has negatively impacted both the technique of top throwers and the development of the event. After studying the trajectory of the hammer head after release by a right handed thrower for selected cases with different safety cage designs, the authors, including Olympic Champion Koji Murofushi, are able prove the existence of a dead zone of approximately 6° inside the landing sector. They explain the calculations they used on data obtained from biomechanical research projects carried out at the IAAF World Championships in Athletics in Tokyo in 1991 and Osaka in 2007. They conclude with proposals for eliminating the dead zone without expanding the current danger zone. They hope their ideas will lead to a dialogue that attracts the viewpoints and opinions of athletes, coaches and others.